Unlocking the Art of Welcome Messages: A Genre Analysis of Welcome Messages on Hotels' Websites - Quesie L. Brigole; Cristelle Mae Descutido; Shekinah Donasco; Chelsea Grace A. Terania; Ruel T. Bonganciso; Devianti Liannita (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
This study is set in a rapidly evolving digital world where websites have become vital, especially in the hotel industry. Hotel industries utilize websites to capture guests' first impressions through a welcome message. As a result, the study probed the typical rhetorical strategies (moves and steps) and the frequently used phrases or clauses in each move and step in the welcome messages on the websites of selected hotels in Western Visayas, where this region is set to claim a significant role in the tourist industry, attracting both local and foreign visitors. Using Google, the researchers used purposeful sampling to gather eligible hotel websites with welcome messages in Western Visayas. For the qualitative data, this study used Swale's Move-Step approach. The result shows that the welcome messages follow a common pattern. The researchers discovered that the corpora have four moves, and each move has one to three steps. These moves and steps represent the typical strategies of hotels' welcome messages. However, the phrases being used, especially the modifiers, vary in their exact formulation but convey the same underlying intention. This study reveals the structured language strategies employed by Western Visayas hotels in their website welcome messages. These findings have implications for ESP education, helping tailor language instruction for the hospitality industry. It aids educators in designing effective language learning strategies in line with evolving communication conventions, enhancing ESP education for specific professions.